Supramolecular assemblies mimicking neutrophil extracellular traps for MRSE infection control. (September 2020) - Huang, Zhentao; Liu, Ye; Wang, Le; Ali, Arbab; Yao, Qingxin; Jiang, Xingyu; Gao, Yuan
Abstract: Neutrophil extracellular traps (NETs) stick to bacteria and prevent infections in vivo, whose activation is upon inflammatory stimuli along with the sudden increase of reactive oxygen species (ROS). Nevertheless, the risky over activation in NETosis may result in deleterious outcome. A big challenge in using NETs for therapeutics is to synthesize an artificial system that can function as NETs in vivo . Here, we developed an in vivo supramolecular assembly system to imitate the innate immune process of NETs to inhibit methicillin-resistant staphylococcus epidermidis (MRSE) infection. Our synthesized small molecules undergo oxidation to form supramolecular nanofibers at inflammatory loci. The in situ formed nanofibers network efficiently traps MRSE cells and prevent them from aggressive dissemination. The extended interactions between nanofibers and bacteria directly result in the death of MRSE via the transcriptomes alterations. In clinically relevant models (intraperitoneal infection and catheter implantation), our supramolecular nets show significant antibacterial activity, yielding a three times efficacy comparing to vancomycin. The spontaneous consumption of ROS and the formation of antibacterial networks create a steady negative feedback system to combat bacterial infections. Graphical abstract: Image 1